Microplastics in the Digestive Tract of Eels (Anguilla sp.) from Lake Poso, Central Sulawesi, and Their Use as Educational Media - Talantu, Felisia; Dhafir, Fatmah; Masrianih; Laenggeng, Abd. Hakim; Rafiqa; Buntu, Amalia (Bioscientist : Jurnal Ilmiah Biologi, 2026)
This study aimed to analyze the occurrence and abundance of microplastics in the digestive tract of eels (Anguilla sp.) from Lake Poso and to implement the findings as an educational poster-based learning medium. A quantitative descriptive method was employed using six eel samples collected from the Pamona area. Microplastic analysis was conducted through organic matter digestion using 10% KOH solution, filtration with Whatman No. 42 filter paper, and microscopic particle identification. The results showed that all samples (100%) were contaminated with microplastics, with a total of 221 particles and an average abundance of 36.8 particles per individual. The identified microplastic types consisted of fibers (56.56%), fragments (23.53%), and films (19.91%), while pellets were not detected. The dominance of fibers suggests that the main sources of contamination were likely domestic and fishing activities around Lake Poso. The research findings were subsequently developed into an educational poster, which obtained an average feasibility score of 84% and was categorized as highly feasible. These findings contribute to scientific knowledge on microplastic contamination in freshwater eels and demonstrate the potential of local research findings to serve as contextual learning resources for improving students’ environmental literacy and awareness.